Chronic Rhinosinusitis with Extensive Recurrent Bilateral Nasal Polyposis-Third Times The Charm - Kamarudin, Intan Kartika; Mohamad Fuzi, Noor Shahira; AlYahya, Syarifah Nafisah; Abdul Wahab, Abdul Fattah; Nik Hussin, Nik Mohd Hazleigh (International Journal of Human and Health Sciences (IJHHS), 2024)
The prevalence of recurrence in chronic rhinosinusitis with nasal polyposis (CRSwNP) is up to 40% after 18 months. Compliance to continuous medical therapy postoperatively is crucial to ensure disease resolution. CRSwNP endotype type 2 which is more common in Caucasian had shown higher recurrence. We report a case with third recurrence and the possible risk factors. A 37-year-old male smoker presented with rhinorrhea, bilateral facial pain, and anosmia for 3 years. He had two previous sinus surgeries and septoplasty. His nasal symptoms recurred a few months after both surgeries. Due to the recent pandemic, he defaulted on follow up. Rigid endoscopy at initial presentation revealed bilateral grade 2 nasal polyps which progressed to grade 4 despite medical polypectomy. Computed tomography of paranasal sinus showed pansinusitis with bilateral extensive polyposis, with presence of frontal intrasinus calcification possibly due to chronic sinusitis or fungal infection. He contracted Covid-19 category 2A infection two months before his planned surgery. The patient underwent bilateral endoscopic sinus surgery revealing extensive polyposis occupying all paranasal sinuses and the nasal cavity, completely obstructing the nasal. Intraoperative blood loss from the mucosa of the sinuses amounted to 2 liters without any arterial bleeding, causing an increase in operative time due to persistent need to secure hemostasis. Histopathological findings showed benign inflammatory polyps. There were reactionary polyps seen in bilateral maxillary sinuses and ethmoids at 2 weeks post operatively. A short course of steroid and chlarythromycin were given to prevent progression of polyps. At 5 weeks post operative, he reported on return of smell, and no more nasal blockage. We discuss the risk factors and endotypes of nasal polyps in recurrence cases with the operative challenges in revision endoscopic nasal surgery. In conclusion, recurrence nasal polyps after revision surgery is multifactorial with some possible prevention. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S55